Tęsknota za Chat Noir i Mirliton. Wokół legendy paryskich kabaretów - Ignaczak, Lidia (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The article invites readers to reinterpret the phenomenon of legendary nineteenth-century Parisian cabarets, inseparably linked to the history of Polish cabarets. The author refers to French sources from the era in order to supplement and verify facts concerning the historical transformation of this phenomenon, while postulating the need for more extensive research on cabaret in the context of its importance for understanding the formation of modern European and Polish popular / mass culture.